Success Factors of Rubberwood as a Furniture Stock in South East Asia - Ratnasingam, Jegatheswaran; Ioras, Florin; MacPherson, T. H. (Journal of the Institute of Wood Science, 2008)
The study evaluated the consumer perceptions towards Rubberwood (Hevea brasiliensis) as a premier furniture material. The data for this study was collected from a questionnaire survey, completed by 250 buyers who attended the international furniture fairs in Malaysia. Correlation analysis showed that the success factors of Rubberwood as a furniture stock are primarily its low cost and ample availability. According to 82% of the respondents, the three major advantages of Rubberwood as a furniture stock in comparison to other furniture wood species are its lower cost, environmental friendliness and workability. Inadvertently, Rubberwood furniture is also plagued by the perception of being low-cost.